The protagonism of Rey in Star Wars: the force awakens, a feminist reading - Allana Cristina Sales Meneses; Margareth Torres de Alencar Costa (Acta Scientiarum. Language and Culture, 2023)
Star Wars is a science fiction saga that for over thirty years has captivated fans and viewers all over the world. The saga reproduces the desires of the current society, decade by decade, and also produces new forms of representation regarding female characters. Although we know names like Princess Leia and Padmé, both had their narratives crossed by negative stereotypes about female representations. As it is a science fiction genre, we still notice a mostly male presence, despite new appearances of heroines. However, it was with the release of The force awakens (Foster, 2015), that the franchise reignited the engagement and interest of the public, besides attracting the eyes of a new generation. In this way, more female characters were cast for the new trilogy, such as the new protagonist being a woman. In the same year, a literary adaptation was launched in the publishing market, bringing the story to the field of letters and providing new dialogues between the characters.  Accordingly, this paper aims to conduct an analytical study on the construction of the character Rey in the literary version of the story, under the light of feminist criticism. For our methodology, we conducted bibliographical research, using authors such as Murdock (2013), Kuhn (1994), and Mulvey (1983).  As a result, we understand that it is important to perceive negative stereotypes reproduced in female characters in science fiction narratives, which are also related to women and their representations in literature.